Landholders' perception of conversion of steep lands to orchard schemes: Land use policy implications in North Iran. (March 2021) - Abdollahzadeh, Gholamhossein; Azadi, Hossein; Sharifzadeh, Mohammad Sharif; Jahangir, Leila; Janečková, Kristina; Sklenička, Petr; Tan, Rong; Witlox, Frank
Highlights: The aim was to analyze landholders' perceptions of threats and opportunities of conversion of steep land to orchard (CSLO). Results showed the most landholders in the study area were well-informed of CSLO threats compared to CSLO opportunities. Reduction of soil erosion and deterioration was the most common perceived opportunities of CSLO. High perception of CSLO threats makes the landholders less supportive of the CSLO scheme· Policy-makers should establish the landholders' trust in long-term program to achieve successful implementation of CSLO. Abstract: This survey study aimed to explore landholders' perceptions of possible threats and opportunities of the CSLO scheme in the Chehel-Chay watershed located in Golestan province, Iran. Furthermore, the influence of these perceptions on the intention to adopt the scheme was assessed. For this purpose, 345 landholders were selected through multi-stage sampling, and the data were collected through a self-administered questionnaire. Results showed that most landholders in the study area were well-informed of CSLO threats rather than CSLO opportunities. For those landholders who cultivate in public land, "the seizure of land ownership by the government" was perceived as the most important threat of CSLO. Furthermore, the contribution of CSLO to the soil erosion mitigation and deterioration was found to be the most frequent perceived opportunity to the CSLO scheme. Based on the findings, the importance of uncertain future costs of implementing CSLO in the rapidly changing Minodasht County should not be ignored by policymakers. This study demonstrated the importance of examining both positive and negative perceptions of landholders about the opportunities and threats of the CSLO scheme. The study concluded that land use policymakers should take into account that the implementation of CSLO has positively contributed to landholders' perception. In other words, the landholders are willing to adopt the scheme. Therefore, policymakers should consider the importance of establishing the landholders' trust in long-term programs.